Precision laser acupuncture at back-shu points enhances growth performance, feed efficiency, and hormonal regulation in rabbits - Mudhita Zikkrullah Ritonga; Ertika Fitri Lisnanti; Widya Pramita Lokapirnasari; Sri Hidanah; Saifur Rehman; Muhammad Fajar Amrullah; Rico Anggriawan; Mutasem Abuzahra; Denny Irmawati Hasan; Aamir Shehzad; Siti Rani Ayuti (Veterinary World)
Background and Aim: Laser acupuncture has emerged as a promising non-pharmacological approach to enhance productivity in livestock. This study aimed to evaluate the effects of laser acupuncture applied to specific back-shu points (Bladder [BL]13, BL15, and BL21) on growth performance, feed conversion ratio (FCR), feed efficiency (FE), and growth hormone (GH) levels in rabbits.